Why is it so hard to implement change? A qualitative examination of barriers and facilitators to distribution of naloxone for overdose prevention in a safety net environment - Drainoni, Mari-Lynn (BMC Res Notes, 2016)
BACKGROUND: The increase in opioid overdose deaths has become a national public health crisis. Naloxone is an important tool in opioid overdose prevention. Distribution of nasal naloxone has been found to be a feasible, and effective intervention in community settings and may have potential high applicability in the emergency department, which is often the initial point of care for persons at high risk of overdose. One safety net hospital introduced an innovative policy to offer take-home nasal naloxone via a standing order to ensure distribution to patients at risk for overdose. The aims of this study were to examine acceptance and uptake of the policy and assess facilitators and barriers to implementation. METHODS: After obtaining pre-post data on naloxone distribution, we conducted a qualitative study. The PARiHS framework steered development of the qualitative guide. We used theoretical sampling in order to include the range of types of emergency department staff (50 total). The constant comparative method was initially used to code the transcripts and identify themes; the themes that emerged from the coding were then mapped back to the evidence, context and facilitation constructs of the PARiHS framework. RESULTS: Acceptance of the policy was good but uptake was low. Primary themes related to facilitators included: real-world driven intervention with philosophical, clinician and leadership support; basic education and training efforts; availability of resources; and ability to leave the ED with the naloxone kit in hand. Barriers fell into five general categories: protocol and policy; workflow and logistical; patient-related; staff roles and responsibilities; and education and training. CONCLUSIONS: The actual implementation of a new innovation in healthcare delivery is largely driven by factors beyond acceptance. Despite support and resources, implementation was challenging, with low uptake. While the potential of this innovation is unknown, understanding the experience is important to improve uptake in this setting and offer possible solutions for other facilities to address the opioid overdose crisis. Use of the PARiHS framework allowed us to recognize and understand key evidence, contextual and facilitation barriers to the successful implementation of the policy and to identify areas for improvement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-016-2268-z) contains supplementary material, which is available to authorized users.